Ensuring patient safety in the new operating theatre of UMMC trauma Centre: an anaesthesiologist novice experience - Mamat, Mafeitzeral; Chan, L. (Faculty of Medicine, University of Malaya, 2009)
Patient safety is a serious global healthcare issue. Harm can be caused by a range of errors or adverse events. Therefore, it is vital that the commissioning of a new operating theatre should comply to the highest standard before it is allowed to function. This paper accounts our experience in the commissioning of the University Malaya Medical Centre (UMMC) trauma centre operating theatre(OT) complex in July 2008. We highlighted the problems we faced in adhering to the international standard guidelines. Unanticipated events were handled professionally and solved. With this experience, we hope that the identified problems would provide suggestions for commissioning an operating theatre in the local setting in the future.